Towards a Zero-Carbon Economy: Societal and Economic Transformations in Sudan - Magda Ali; Amin Yasin (International Journal of Sudan Research, 2025)
Purpose: This study examines how Sudan can meet international emission reduction targets and transition to a zero-carbon economy, despite financial and technical challenges. It explores strategies for aligning with global agreements such as the Paris Agreement, integrating environmental concerns into economic planning, and fostering cultural change to support the transition. Methodology: The research is based on qualitative secondary data, focusing on social and economic transformations. It highlights both formal and informal efforts to promote a zero-carbon economy and addresses barriers to full implementation. Findings: Sudan has made significant efforts, both formal and informal, to transition to a zero-carbon economy. However, the lack of co-ordination and the absence of a unified platform to organise these efforts have weakened their impact, preventing the anticipated economic and social transformation from being achieved. Originality: This study contributes new insights into Sudan’s unique challenges, including conflict, instability, and limited data, while highlighting the role of social and economic factors in achieving a zero-carbon economy. Limitations: Data access, especially in rural areas with active projects such as the Mukhrebish Forest Regeneration and Acacia Gum Belt, and the political environment, limit data collection and policy implementation. The study urges socio-economic reform and provides practical guidance for policy-makers and development partners to support Sudan’s green transition by 2030. Keywords: Zero-Carbon Economy; Renewable Energy; Sustainable Development; Socio-Economic Transformation. Citation: Ali, M.M.S. and Yasin, A.S. (2026): Towards a Zero-Carbon Economy: Societal and Economic Transformations in Sudan. International Journal of Sudan Research (IJSR), Vol 13, Nos. 1/2, pp. 37-50.